Analysis of Factors Influencing Investor Interest in Investing in Mutual Funds Through the Bibit Application - Tazkiyah, Aufa; Fauziah, Fitri Ella (Accounting Study Program, Faculty of Economics and Business, 2024)
Among Indonesia's most prominent investment platforms is the Bibit application, which specializes in mutual fund investments and caters primarily to novice investors. This research seeks to explore the effects of Investment Benefits (X1), Investment Knowledge (X2), Minimum Investment Capital (X3), and Features of the Bibit Mutual Fund Application (X4) on Investor Interest in investing in mutual funds via the Bibit app (Y). The study adopts a quantitative methodology, targeting individuals who have used the Bibit app to invest at least once, are 18 years or older, and live in Java. A total of 150 respondents participated, with data gathered through questionnaires as primary data and supported by secondary sources such as books, academic journals, websites, and other documents. Using multiple linear regression analysis with SPSS version 25 software, the findings revealed that although Investment Benefits had a positive correlation with investor interest, this influence was not statistically significant. Conversely, variables such as Investment Knowledge, Minimum Investment Capital, and Application Features were found to have a significant positive impact on investor interest in mutual funds through the Bibit platform.